Politik Hukum Pemberantasan Tindak Pidana Narkotika di Masa Pandemi Covid-19 (Studi Polda Sumut) - Rahmad Gaol Hasibuan; Rizkan Zulyadi; M. Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Narcotics crimes are included in extraordinary crimes (extraordinary crime). Cases of narcotics abuse during this pandemic are increasing, from 2019 to 2020. The increase in narcotics circulation during the COVID-19 pandemic can be seen from the increasing number of evidence of narcotics being caught which is getting higher. This study aims to determine the modus operandi of narcotics trafficking and abuse during the Covid-19 pandemic. The research method used is normative juridical. The data used is secondary data consisting of primary, secondary and tertiary legal materials. Qualitative data analysis is used in analyzing the problem. The results of the study found that first, the modus operandi of narcotics trafficking and abuse during the Covid-19 pandemic had developed, namely by sending three bottles of narcotics in the form of liquid from China containing 10 ml which read Hemp Oil, Drug abuse is carried out in homes, apartments, and hotels. session, the modus operandi is to use postal and expedition services to several areas, and via online with a website, besides that, the mode of circulation is by means of agricultural logistics transportation, as if sending goods for the needs of the community.